Servitization in Germany – Establishing the context of servitization in manufacturing firms - Kurtz, Julian; Meyer, Patrick; Roth, Angela (Proceedings of the 9th International Conference on Business Servitization (ICBS 2022), 2022)
This book of abstracts summarizes the proceedings of the 9th International Conference on Business Servitization (ICBS 2022), held at Hotel Ilunion, Malaga, Spain. On this edition, the conference places a special emphasis on the focal theme: Servitization as a springboard for enhancing Sustainable manufacturin
Keywords: Servitization; Service Systems; Digital Transformation